FROM SCROLLING TO SEARCHING: MODELING AFFORDANCES, CREDIBILITY, AND MISINFORMATION RISK IN GEN-Z’S TIKTOK-BASED F&B SEARCH BEHAVIOR - Agung Stefanus Kembau; Ongky Alex Sander; Yunitalia Yunitalia (Jurnal Manajemen Pemasaran, 2026)
TikTok increasingly functions as an experiential search environment for Indonesian Gen-Z, shaping how food and beverage information is evaluated and acted upon. This study examines how perceived affordances and perceived search value shape perceived credibility, and how credibility and search satisfaction, in turn, drive visit intention. It also tests whether perceived misinformation risk weakens the credibility–intention pathway. A cross-sectional survey of Gen-Z TikTok users in Greater Jakarta (N = 234) was analyzed using partial least squares structural equation modeling. Results show that search value (β = 0.35, p < .001) and affordances (β = 0.28, p < .001) increase credibility; credibility raises search satisfaction (β = 0.41, p < .001), and both credibility (β = 0.32, p < .001) and satisfaction (β = 0.37, p < .001) heighten visit intention. The model explains a substantial share of variance in visit intention (R² = 0.56) and exhibits predictive relevance. Moderation tests indicate that misinformation risk reduces the behavioral impact of credibility (β = −0.17, p = .008). The study contributes a coherent mechanism linking platform design and experiential value to credibility, satisfaction, and behavior, and identifies platform-level skepticism as a boundary condition for conversion. For managers, the findings imply that designing high-fit, low-friction discovery episodes and embedding transparent verification cues are essential to translate short video search into offline visits.